Review of ophthalmology undergraduate teaching curriculum - Sivanthi Kanagasundaram (Journal of Clinical Ophthalmology and Research)
The undergraduate ophthalmology teaching curriculum within UK medical schools is eroding, with discrepancies among UK medical schools in the exposure to ophthalmology teaching. Understanding how medical schools currently assess competency in ophthalmology helps determine whether these methods are adequate to address the ever-increasing prevalence of eye conditions in the general population. A review of existing literature on the undergraduate ophthalmic medical curriculum was conducted. All relevant literature cited on PubMed and Google Scholar in the English language was reviewed with keywords “Undergraduate Ophthalmology Curriculum” and “Ophthalmology in Medical School.” The inclusion criterion was the ophthalmology curriculum in medical schools in the UK. The exclusion criteria were virtual curriculums adopted during COVID-19 and postgraduate ophthalmology curriculum. The current design of the ophthalmology curriculum in UK medical schools and its fitness for purpose will be critically analyzed with the major schools of the educational theory underpinning the findings. There is a lack of standardized ophthalmic curriculum across UK medical schools, with each institution interpreting the General Medical Council (GMC) framework differently. Undergraduate ophthalmic education seems to be underpinned by competency-based medical education. Although the goals of the curriculum appear to be aligned with the outcomes set out by the GMC, it can be argued that this is merely superficial. The curriculum adopted by UK medical schools allows students to demonstrate competency in the required skills outlined by policymakers. The interpretation of the ambiguous framework has resulted in the undervaluation of the ophthalmic curriculum. To address this issue, governing bodies should consider promoting a standardized curriculum with clear definitions of pathologies students should be familiar with.